Impact of Ground-Applied Termiticides on the Above-Ground Foraging Behavior of the Formosan Subterranean Termite - Henderson, Gregg (Insects, 2016)
We conducted a laboratory study to determine the impact of ground-applied termiticides on the above-ground foraging behavior of Coptotermes formosanus. Two concentrations (1 and 10 ppm) each of three termiticides, viz. fipronil, imidacloprid and chlorantraniliprole, were tested. After one month post-treatment (fipronil 10 ppm was run for 12 days only and all other treatments were run for one month), fipronil had the lowest percentage of survival (3%–4%) at both concentrations. Termite survival ranged from 31% to 40% in the case of imidacloprid treatments and 10 ppm chlorantraniliprole. However, 1 ppm chlorantraniliprole did not cause significant mortality compared to the controls. Foraging on the bottom substrate was evident in all replicates for all chemicals initially. However, a portion of the foraging population avoided the ground treatment toxicants after several days of bottom foraging. Only the slower-acting non-repellents created this repellent barrier, causing avoidance behavior that was most likely due to dead termites and fungus buildup on the treated bottom substrate. Fipronil appeared more toxic and faster acting at the concentrations tested, thus limiting this repellent effect. Suggestions by the pest control industry in Louisiana that some non-repellents can create a repellent barrier stranding live termites above ground are supported by this laboratory study.